Problematika Guru Sejarah Dalam Implementasi Pembelajaran Jarak Jauh (PJJ) Pasca Pandemi Covid-19 - Sudarsono, Yohanes Bagus; Novarianto, Rizki Agung (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
The Covid-19 pandemic that has hit the world including Indonesia requires taking astance to prevent wider transmission, including the education sector. In relation to this,the Ministry of Education and Culture has taken a firm stance through several circularsregarding education policies during the emergency period of the spread of Covid-19.This article examines the implementation of education policies during the Covid-19pandemic related to distance learning policies. The distance learning process is asolution that has not been optimally implemented overall during and after thepandemic. There are things that must be considered in this distance learning, includingthe quality of teacher resources must be improved, both in terms of teaching style,content, learning methods, learning media and methodology as well as in terms of theuse of information technology. In addition, students are also less active in participatingin this distance learning, either due to an unstable internet network or in terms of theprovision of limited internet quota. The purpose of writing this article is to study andunderstand the problems in learning activities during the pandemic, namely distancelearning so that students can participate actively and interestingly. This study uses aqualitative and observational approach. The results of this study prove that distancelearning (PJJ) during the Covid-19 pandemic has given rise to various responses andchanges in the learning system which can affect the learning process and the level ofdevelopment of students in responding to the material presented.